A Modified Enucleation and Deflation to Treat Large Ameloblastoma in the Mandible - Andi Setiawan Budihardja; Bakhrul Lutfianto (Case Reports in Dentistry)
Objective. Treatment of large ameloblastoma with a conservative method. Case Presentation. Ameloblastomas are benign tumors of odontogenic origin. These tumors are locally invasive with a high recurrence rate. This case report will present a conservative approach to treating large ameloblastoma in the mandible using modified enucleation and deflation technique. The patient presents with a recurrence of large unicystic ameloblastoma. The following patient is treated with the two-stage enucleation and deflation technique. One-year post-treatment follow-up shows satisfactory healing, with good bone regeneration in the defected area, showing no signs of recurrence. Conclusion. The technique that will be discussed in this case report provides an alternative treatment for ameloblastomas of the mandible. This approach can avoid radical operative procedures, such as jaw resection and bone reconstruction.